If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 12y = -40 Solving X + 12y = -40 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12y' to each side of the equation. X + 12y + -12y = -40 + -12y Combine like terms: 12y + -12y = 0 X + 0 = -40 + -12y X = -40 + -12y Simplifying X = -40 + -12y
| (x+7)(x+7)=-14 | | 16.40=x-0.20*x | | 0.5P-10=50-P | | -8-7(r-6)=90 | | d=5m | | 2+5x=6x-8 | | 17x+11=180 | | 18x+4=180 | | x-8=2x-14 | | 16.40=x-020*x | | 1/3x35x7 | | 3x-(6x-4)/2=-2 | | -2.5-3y=-3 | | 9n^2-18n-16=0 | | 5x-2x-2=3x-9 | | 13+11x=360 | | 684=0.14x+0.10(1800+x) | | 11=1-2x | | 0.3x-0.5=0.2x+6 | | a^2-26=0 | | -6*3b+3+19b-6=0 | | 0=2x^2-8x | | 13+11x=180 | | Log^2(x+3)=4 | | 31/2r=28 | | 11x-4=360 | | -4x-11=2(x-3x)+13 | | x+0.10(600-x)=.55(600) | | 13.2=t-4.4 | | 0=-16t^2+38 | | 3n^2-n-14=0 | | 3(7x+4)=21x+21 |